Faktor-Faktor yang Memengaruhi kepuasan Pelanggan Bengkel Ahass Area Bantul - Fikri Farhan; Guruh Ghifar Zalzalah; Murgiyanti Murgiyanti (Universitas Putera Batam, 2023)
in the Bantul area of Yogyakarta. Service quality, facilities, and product quality are hypothesized to influence customer satisfaction. This study uses quantitative methods. The primary data is collected through questionnaires to 160 consumers who have used repair or replacement services for their motorcycle parts at the AHASS repair shop in the Bantul area of Yogyakarta. The data in this study were processed using the SPSS analysis tool with multiple linear regression techniques. The results showed that service quality, facilities, and product quality positively and significantly affected customer satisfaction.